The duty to believe according to the evidence - Wood, Allen W. (International journal for philosophy of religion, 2008)
‘Evidentialism’ is the conventional name (given mainly by its opponents) for the view that there is a moral duty to proportion one’s beliefs to evidence, proof or other epistemic justifications for belief. This essay defends evidentialism against objections based on the alleged involuntariness of belief, on the claim that evidentialism assumes a doubtful epistemology, that epistemically unsupported beliefs can be beneficial, that there are significant classes of exceptions to the evidentialist principle, and other shabby evasions and alibis (as I take them to be) for disregarding the duty to believe according to the evidence. Evidentialism is also supported by arguments based on both self-regarding and other-regarding considerations.